Civilisation, civilité, profanation - Pierre Antoine Fabre (Nuevo mundo - Mundos Nuevos, 2023)
This essay examines the interweaving of the notions of "civilization" and "evangelization", intersecting them with those of "civility" and "profanation" in the long history of modern colonization and contemporary anthropology. His project, to be pursued, is to lift both the taboo of the anthropology underlying modern ethnography and that of the underground exchanges between missionary churches and the activity of anthropologists in the contemporary era. For this exploration, he calls on figures who are rarely brought together, such as Guillermo Furlong and Maurice Leenhardt.